2016
DOI: 10.1108/wjemsd-03-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Issues and constraints perceived by young entrepreneurs of Pakistan

Abstract: Purpose – The purpose of this paper is to find out intentions of business graduating students regarding launching their own business, and their perception regarding issues and constraints entrepreneur would encounter after entering into entrepreneurial activities. In addition, it focusses to provide a general understanding regarding entrepreneurship. The study also argues unfriendly policies and environment for entrepreneurship slows down poverty reduction and economic development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
1
19
1
Order By: Relevance
“…The effect of self-efficacy on entrepreneurship intention is not significant for both of the student. These results do not support the results of research conducted by (Minuto, 2018); (Bharanti, 2016); (Indarti & Krinstiansen, 2018), (Aslam & Hasnu, 2016), (Rachmawan et al, 2015). The interpretation of the results of this analysis is that self-efficacy is not a predictor for business and engineering students.…”
Section: Discussion / Analysiscontrasting
confidence: 93%
See 2 more Smart Citations
“…The effect of self-efficacy on entrepreneurship intention is not significant for both of the student. These results do not support the results of research conducted by (Minuto, 2018); (Bharanti, 2016); (Indarti & Krinstiansen, 2018), (Aslam & Hasnu, 2016), (Rachmawan et al, 2015). The interpretation of the results of this analysis is that self-efficacy is not a predictor for business and engineering students.…”
Section: Discussion / Analysiscontrasting
confidence: 93%
“…People who have an internal locus of control can have entrepreneurial intentions and choose to become entrepreneurs (Karabulut, 2016). Therefore, (Aslam & Hasnu, 2016) internal locus of control is very important to decide to start a business. On the other hand, individuals with strong external controls tend to have the perception that their decision, including their entrepreneurship intention, is affected by external factors such as luck, opportunity, fate or others (Samydevan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also shapes their decision-making processes, desires, and courage or confidence in taking and responding to the risks at hand Tong et al (2011). To become entrepreneurs, students also need to have high self-efficacy, which is related to the belief in his/her abilities (Aslam & Hasnu, 2016) and, consequently, determines their way of thinking, persistence in action, and ability to motivate themselves when facing difficulties (Asmara et al, 2016). Dalimunthe et al (2019) also revealed that self-efficacy greatly affects students' motivation to achieve success or goals.…”
Section: Findings and Discussion Validity And Reliability Test Resultsmentioning
confidence: 99%
“…The youth in Pakistan is most agonized segment of the population which needs special policies and strategies towards social, cultural and economic development (Shaukat & Hameed, 2016). Aslam and Hasnu (2016) argued that government of Pakistan procured various steps for making the youth conditions as much as sophisticated in which the entrepreneurship development is the most significant initiative. The government of Pakistan offered various chances for development to young entrepreneurs to come across and utilize their knowledge and skills by availing diverse business opportunities to make their condition better and to contribute in economic development of Pakistan (Mahmood et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%